Evaluation of antinuclear antibodies of SLE panel in COVID-19 patients: a cross-sectional study in a tertiary care hospital / K Usha Krishnan ... [et al.] - Krishnan, K Usha; Mary, D Therese; Ananthakrishnan, P; Ravinder, Thyagarajan (Faculty of Medicine, 2025)
Introduction: COVID-19, caused by SARS-CoV-2, has raised concerns about its potential to trigger autoimmune phenomena and post-inf ection autoimmune diseases. This study aimed to assess the prevalence and patterns of antinuclear antibodies (ANA) in post COVID-19 patients. Methods: A cross-sectional study was conducted f rom August to October 2021, involving 108 adult post COVID-19 patients with articular and musculoskeletal symptoms. ANA screening was perf ormed using the Indirect Immunof luorescent Test (IIFT) with HEp-2 cell substrate, and positive samples were f urther analyzed using Line ImmunoAssay (LIA) f or specif ic ANA detection. Demographic data and disease severity inf ormation were collected. Results: Among the participants, 29% tested positive f or ANA by IIFT, and 17% of those with 3 months post COVID-19 and 37% with >6 months post COVID-19 were ANA-positive. LIA confirmed ANA positivity in 18 patients. The most common ANA pattern was nuclear speckled (52%), f ollowed by homogenous (21%), DFS 70, and Nucleolar (10% each), and Cytoplasmic (7%). The prevalence of ANA increased signif icantly with longer post COVID-19 duration (>6 months vs. 3 months, p = 0.017) U1 snRNP-related speckled pattern was most f requent. However, the study f ound no correlation between ANA patterns and post COVID-19 duration. Conclusion: The f indings suggest that COVID-19 may trigger the development of ANA autoantibodies, especially in patients with a longer post-inf ection duration. Long-term f ollow-up studies are essential to understand the role of ANA in inf ection-triggered autoimmune conditions, enabling early diagnosis and treatment.